Pengaruh Dukungan Sosial dan Dukungan Organisasi terhadap Kinerja Karyawan Melalui Komitmen Afektif - Cahyasatrio, Lifito Rizki; Senoaji, Pandu Arya; Siddiq, Dedi Muh; Asyifa, Eteh Resa (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of social support and organizational support on the performance of car rental driver employees in Cirebon City, with affective commitment as a mediating variable. The study is grounded in the phenomenon of low performance stability, high absenteeism, and fluctuating productivity among drivers, which indicate weak emotional attachment to the organization. This research adopts a quantitative associative approach using a survey method on 200 car rental drivers selected through purposive sampling. Data were collected through a validated and reliable questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that social support and organizational support have a positive and significant effect on employee performance, both directly and through affective commitment. Affective commitment explains 63% of the variance in itself and contributes to 69% of the variance in employee performance. These findings confirm that strengthening social support and organizational support enhances affective commitment, which in turn improves the performance of car rental drivers in Cirebon City.